Preoperative Psychometric Properties of PROMIS Upper Extremity, Pain Interference, and Depression in Bankart Repair and Rotator Cuff Repair (115). Issue 10 (31st October 2021) - Vadhera, Amar; Beletsky, Alexander; Singh, Harsh; Chahla, Jorge; Cole, Brian; Verma, Nikhil
Objectives: To examine the preoperative and postoperative performance of PROMIS Upper Extremity 2.0 across various orthopedic procedures for the upper extremity. Secondarily, to define susceptibility to pre- and post-operative floor and ceiling effects. Methods: Retrospective analysis of prospectively collected patient-reported outcome (PRO) data was conducted utilizing an electronic outcome registry for procedures between May 2017 and August 2018. Current procedural terminology (CPT) codes were utilized to examine cohorts for various upper extremity orthopedic procedures including Bankart repair and arthroscopic rotator cuff repair (ARCR). Shapiro-Wilks normality testing was used to assess score distributions for normalcy; given non-normal score distributions, Spearman correlation coefficients were calculated for preoperative patient-reported outcome (PRO) scores. Absolute floor and ceiling effects were calculated for each time point based on CPT code. Results: A total of 488 patients were included across Bankart repair (n=109, 29.3+ 12.5 years) and ARCR (n=379, 57.5+ 9.5 years) cohorts. In the Bankart repair cohort, PROMIS PI demonstrate strong correlations with ASES (r=-0.63), Constant (r=-0.75), PROMIS UE (r=-0.75), and the VR6D (r=-0.61). PROMIS Depression (r=0.23 vs. 0.17), SF12 MCS (r=0.34 vs. 0.11), and VR12 MCS (r=0.44 vs. 0.15) exhibited poor correlations with PROMIS PI and UE, respectively. In the ARCR cohort, PROMIS PI scores demonstrated a good correlation with PROMIS UE (r=0.61). Constant (r=0.58 vs. 0.67), VR12 PCS (r=0.58 vs. 0.47), and VR6D (r=0.67 vs. 0.53) exhibited good correlations with both PROMIS PI and UE measures, respectively. No significant absolute floor or ceiling effects were observed for the PROMIS instruments except PROMIS Depression; an absolute floor was noted for both Bankart (n=12, 30%) and ARCR (n=38, 14.7%) groups. Conclusions: PROMIS PI and UE instruments perform comparably to legacy outcome instruments in patients receiving Bankart repair, as well as those receiving ARCR. Furthermore, in both populations, the PROMIS Depression instrument exhibits absolute floor effects, whereas PROMIS PI and UE instruments fail to demonstrate any absolute floor or ceiling effects.